Analysis of Overclaim Practices in Skincare Products: Review from Moral, Business Ethics, and Legal Protection Perspectives - Mugisana, Radi; Septifani, Eneng Nurdiana (Entrepreneurship and Small Business Research, 2024)
In the contemporary digital marketplace, the rapid expansion of the skincare industry has intensified concerns over exaggerated product claims and the erosion of consumer trust. Overclaiming has become increasingly visible in Indonesia, particularly through aggressive digital marketing and influencer endorsements. This study aims to analyze overclaim practices in skincare products from the perspectives of morality, business ethics, and consumer legal protection, while examining the legal consequences for business actors under Law No. 8 of 1999 on Consumer Protection and BPOM Regulation No. 25 of 2025 on Technical Requirements for Cosmetic Ingredients. Employing a qualitative descriptive method combined with a normative juridical approach, the research utilizes documentation of laboratory-test-based educational content from the TikTok account @dokterdetektif as primary empirical data, supported by relevant legal and academic sources. The findings reveal significant discrepancies between advertised claims and laboratory results in several brands, indicating violations of ethical principles such as honesty, transparency, and social responsibility. Overclaim practices generate social distrust, economic loss, health risks, and potential civil and criminal liabilities for business actors. This study contributes by offering an integrated moral–legal accountability framework that links digital-era marketing practices with consumer protection enforcement, thereby enriching the discourse on ethical governance and sustainable business conduct in the skincare industry.